A NATION IN FLUX: MIGRATION, ISLAM AND THE REDEFINITION OF GERMAN NATIONAL IDENTITY - Alamshah, Anisah; Suarayah; Syamsadduha Saleh; Yasse Mulla Shadra (Program Studi Sejarah Peradaban Islam, 2024)
Germany, being the Western nation with the largest Muslim population in Europe - estimated at approximately 5.3 to 5.6 million people based on 2021 data from the Federal Office for Migration and Refugees (BAMF) - has implemented highly restrictive and exclusive government policies toward Muslim immigrants. As a result, Islamophobia cases frequently grab headlines in German media, closely linked to the breakdown of multicultural policies that have fostered a negative portrayal of Islam. These cases often serve as manifestations of societal tensions and prejudices, exacerbating the perception of Muslims as the ‘other’ within German society. Based on descriptive research that depicts ongoing phenomena and aims to uncover the roots of discrimination in Germany, the study results indicate that through a deeper historical examination, Germany indeed has significant interactions with the Muslim world despite not having colonies. Multiculturalism in Germany, contrasting with its history, is believed to have emerged after World War II. A labor shortage prompted a substantial influx of immigrants, primarily from Africa, seeking work opportunities. Many arrived with their families, belonging to African ethnic groups and practicing Islam, contributing to the diverse fabric of Germany. This immigration-induced diversity played a pivotal role in shaping Germany into a multicultural society. As the immigrant populace continued to grow, its presence exerted influences on societal, political, and cultural landscapes. Social disparities between locals and immigrants sparked tensions, culminating in conflicts within shared living spaces and resulting in discriminatory and racist behaviors